THE EFFECTS OF COPPER AND ZINC IONS DURING THEIR BINDING WITH HUMAN SERUM γ-GLOBULIN - S. B. Cheknev; E. E. Babaeva; A. E. Golub; E. A. Denisova; U. A. Vorobieva (Медицинская иммунология, 2014)
Abstract. Conformational changes of human serum γ-globulin were studied during and after its binding with copper and zinc ions, using molecular ultrafiltration and differential spectrophotometry. The contents of nonbound metals in the filtrate were evaluated, resp., with sodium diethyl thyocarbamate and o-phenanthroline. It has been shown that copper and zinc exhibited common biological properties during their interactions with protein, but the binding differed sufficiently under similar experimental conditions. E.g., it was confirmed that copper was more active at the external sites of γ-globulin molecule, whereas zinc demonstrated tropicity for the areas of protein intraglobular compartments. The metal-binding sites have been described that differ in their parameters of interactions with cations and their spatial location within globular domains. Approaches are suggested for dynamic analysis of saturation for these differently located sites by the metal ions. We discuss the issues of altered conformational state of the γ-globulin molecule during the binding of cations, as well as potential usage of these data in clinical immunology.